Phosphorylated Neurofilament Heavy Chain Correlations to Visual Function, Optical Coherence Tomography, and Treatment. (26th December 2010) - Pasol, Joshua; Feuer, William; Yang, Cui; Shaw, Gerry; Kardon, Randy; Guy, John
Abstract : Objective . To correlate visual and neurologic clinical scores and treatment of optic neuritis and multiple sclerosis (MS) patients with assays of serum phosphorylated neurofilament heavy chain (pNF-H) and optical coherence tomography (OCT) measurements of axonal loss. Design/Methods . The Optic Neuritis Treatment Trial (ONTT) randomized 457 patients with acute optic neuritis to intravenous methylprednisolone (IVMP) followed by oral prednisone, oral prednisone or placebo treatment arms. We quantified serum pNF-H levels in 175 ONTT patients 5 years after study entry. We performed OCT measurements of macular volume and the retinal nerve fiber layer (RNFL) in a subset of 51 patients at year 15. Results . Elevated pNF-H levels at year 5 correlated to poorer visual function at study entry. Lower 15 year macular volumes and RNFL thickness correlated better with follow-up than with baseline visual function measures. With IVMP treatment, 15 year RNFL differences of the fellow eye (FE) minus the affected eye (SE) RNFLFEmSE correlated with five-year pNF-H levels. PNF-H was reduced by half with IVMP relative to placebo or by 40% relative to prednisone. Conclusions/Relevance . Acute optic neuritis patients who have more severe visual loss during initial presentation have a higher incidence of axonal loss that was slightly suppressed with IVMP treatment.